A generalization of the dichromatic polynomial of a graph - E. J. Farrell (International Journal of Mathematics and Mathematical Sciences)
The Subgraph polynomial fo a graph pair (G,H), where H⫅G, is defined. By assigning particular weights to the variables, it is shown that this polynomial reduces to the dichromatic polynomial of G. This idea of a graph pair leads to a dual generalization of the dichromatic polynomial.